Architectural research methods - Groat, Linda; Wang, David (New Delhi John Wiley & Sons, 2013)
The leading text on architectural research, Architectural Research Methods, Second Edition is completely revised throughout to include current trends and innovations in research, and discusses interdisciplinary involvement with design/build, sustainability and policy, urban design, product design, and product systems. This practical guide for architects and designers employs real-life examples of how good research can be used, from project inception to completion. New coverage of design studio-based research shows how the strategies described can be employed while new discussion of the use of digital media help frame the scope of research.
Keywords: SCOPEOFTHISBOOK; DOESDESINGEQUALRESEARCH; SYSTEMSOFINQUIRYANDSTANDARDSOFRESEARCHQUALITY; PROFESSIONAL PRACTICE (AR-PP)